STRATEGI PENGURUS ANAK CABANG (PAC) MENGGUNAKAN Methode Sainte Lague DALAM UPAYA MENINGKATKAN PEROLEHAN SUARA PARTAI DEMOKRASI INDONESIA PERJUANGAN (PDIP) PADA PEMILU LEGISLATIF TAHUN 2019 DI KECAMATAN MARGA, KABUPATEN TABANAN - Sri Candrawati, Anak Agung Ketut; Artha Wibawa, I Ketut Sukantha (Universitas Panji Sakti, 2025)
Abstract- Departing from the problems that occurred and the spirit of guarding democracy in the future, the PDI Perjuangan Branch Manager (PAC) in an effort to increase the number of votes in the 2019 legislative elections in Marga sub-district, Tabanan Regency, and the PDI Perjuangan PAC's strategy in winning the 2019 elections. using the conversion of party votes to seats (Sainte Lague Method) which is the background for this research. This research uses a descriptive qualitative research method, the research describes the condition of the subject and object, both an institution/organization. The offensive strategy includes efforts to penetrate the voter market and expand the voter market to increase the party's vote share. Meanwhile, the defensive strategy includes efforts to maintain support from existing voters, which includes strict internal supervision, protection against legal and political attacks, voter involvement and education by voter mobilization teams (Guraklih). Research conclusions and suggestions The strategy implemented by the Sub-Branch Management (PAC) of the Indonesian Democratic Party of Struggle for Marga Subdistrict in winning the 2019 Election focuses on two approaches, first an offensive strategy and second a defensive strategy. Marga Sub district PDI Perjuangan PAC research should continue to develop and strengthen training, coaching and evaluation programs for cadres on a regular basis.